Acesso à justiça do trabalho pela via dos direitos: um olhar sobre a aplicação do jus postulandi no contexto amazonense - Dorinethe dos Santos Bentes (2023)
The present research aims to demonstrate whether jus postulandi in the current Brazilian labor justice system is capable of providing access to justice through workers' rights, analyzing the effectiveness of jus postulandi as an instrument of access to labor justice in the Amazonian context, in the period from 2016 to 2020, using as a sample scenario the 10 (ten) Labor Courts that operate in the interior of the state of Amazonas. The development and elaboration of the thesis was guided by the sociological legal aspect guided by dialectical scientific reasoning, supported by the proposal developed by UFMG professors, Leonardo Avritzer; Marjorie Marona; Lilian Gomes, of access to justice through rights, involving the dimensions of expanding the realization of rights and expanding the possibility of participation in the conformation of rights, focused on labor relations. To expand the theoretical range of the debate, the attentive lens of the theory of decoloniality and the paradigms of dialogical reason and complexity were used to analyze access to justice through rights in the Amazonian context. The methodology developed in the research was the analysis of primary sources (labor processes stored in the database of the PJe-JT system of the 11th Regional Court). 29,474 processes were analyzed, corresponding to processes initiated in the Labor Courts of Coari (2,109 processes), Eirunepé (1,014 processes), Humaitá (2,239 processes), Itacoatiara (3,322 processes), Lábrea (1,175 processes), Manacapuru (4,511 processes), Parintins (4,649 processes), Presidente Figueiredo (2,647 processes), Tabatinga (3,881 processes), Tefé (3,926 processes), in addition to conversations with the employees of the respective Courts. These Courts were chosen because they operate in the interior of the state and are the only ones with physical installations in these locations. These 10 (ten) Courts serving the jurisdiction of the 61 municipalities in the interior of Amazonas and dialogues with the civil servants who act directly in the actions initiated through the jus postulandi (servants from the atermation sector, court directors, judges and the civil servants who monitor the audiences) make up the sampling frame. The results obtained from the research are that jus postulandi is a legal instrument capable of providing access to jurisdiction considering that the average access to the 10 Courts through jus postulandi was above 50%, considering that the Court with the lowest index 22 % was in Manacapuru and the highest rates were in the Tabatinga Courts 70% and Tefé 68%. It is also capable of providing access to justice through rights, in its two dimensions of effectiveness and participation. Workers who took legal action through jus postulandi had their rights guaranteed through agreements approved between the parties or by sentences. One factor that stood out in the consolidated research data was the self-resolution rate at the first hearing through agreements between the parties. The data produced in the research reinforced the argument that jus postulandi, in addition to providing access to labor jurisdiction, also enables access to law, as advocated by the expanded concept of access to justice through rights, which encompasses the dimensions of enforcement, participation and proposition. In addition to the results initially proposed for scientific research, the practical results of this work stand out, such as the creation of markers to identify jus postulandi and Itinerant Justice within the PJe system from the beginning to the end of the process.